(untitled) (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2018)
Wilkie Collins’s The Woman in White (1860) and Oscar Wilde’s The Picture of Dorian Gray (1890) are novels significant for their distinct awareness of the socio-political power of the gaze. In this essay, I will reveal how these authors use the male and female gaze in similar and contrasting ways. In particular, I shall explore the ways they denounce the patriarchal Victorian system, which renders the act of gazing a power that is both objectifying and degrading. Gazing enacts itself to varying degrees through the social hierarchy, indicating whom can objectify whom, and can enact upon what they choose to see. This hierarchy of Victorian English society is so varied by class, wealth, gender, and race that the gaze in these texts does not always operate in the same way. These complicated intricacies of the gaze are what make these novels require such in-depth analysis, because of the multiple ways in which the gaze can work according to individual scenarios. Both authors portray these complicated intricacies by using both the male and female gaze in the text. While academic critique usually separates these two gazes due to their gender, the novels of Collins and Wilde reveal how important it is to study them together, because while the gaze affects people individually, it is essentially a collective interaction. Collins and Wilde take separate approaches in depicting the gaze: the former testing the capability of the reader to look beyond the coercive statements of the first-person narrator, and the latter an omnipresent third-person narrator. Together, these different approaches increase reader understanding of the mechanical workings of the gaze and therefore complements a comparative analysis of the two novels.